A study of the influence of additives on the process of formation and corrosive properties of tripolyphosphate coatings on steel - Vlasova, Elena; Kovalenko, Vadym; Kotok, Valerii; Vlasov, Sergey; Sukhyy, Kostiantyn (Eastern-European Journal of Enterprise Technologies, 2017)
The anodic behavior of coldrolled lowcarbon steel in the aqueous STPP solution with aluminum hydroxide, borax, and glycerin additives at room temperature has been studied. It was revealed that the potentiodynamic curves that characterize the anodic behavior of steel st05kp samples show<s>s</s> up to three passivation plateaus. Additionally, the anodic curve ends with the complete passivation plateau with an anodic current density equal to zero. The obtained results demonstrate realization of the stepwise formation mechanism of tripolyphosphate coat in the 12 % aqueous STPP solution with additives. It was found that with the addition of 2 % Al(OH)3, a narrowing of the first passivation plateaus is observed. The addition of glycerin shifts the potential of passivation plateau formation toward negative values by about 150 mV. When borax was added, only the complete passivation plateau is present on the anodic curve. It was established that in the STPP solution with the addition of aluminum hydroxide, glycerin, and especially borax, steel passivation occurs earlier than in the solution without additives. This indicated the acceleration of tripolyphosphate coat formation when additives are used. The absence of the first two passivation plateaus on the anodic curve that describes the coat formation in the STPP solution with the borax additive indicated that formation occurs at the highest rate. In the process of studying the anodic behavior of steel st05kp with the formed coats, in 0.1 N Na2SO4, it was found that the coats formed in the aqueous sodium tripolyphosphate solution with additives possess protective properties. The greatest positive effect on protective properties of the coats is provided by aluminum hydroxide. Based on the results of combined studies, it was established that aluminum hydroxide can be recommended as the most effective additive for improving protective properties of tripolyphosphate coats. Borax can be recommended as an additive that accelerates coat formation.